A Unified Interdisciplinary Approach to Design Antibacterial Coatings for Fast Silver Release. Issue 8 (11th May 2017) - El Arrassi, A.; Bellova, P.; Javid, S. M.; Motemani, Y.; Khare, C.; Sengstock, C.; Köller, M.; Ludwig, A.; Tschulik, K.
Abstract: The increasing number of surgical treatments performed per year requires novel approaches to inhibit implant‐associated infections, caused by multi‐antibiotic resistant bacteria. Silver ions (Ag + ) are known for their effective antimicrobial activity. Therefore, a system that efficiently and locally releases the minimum required amount of Ag + directly after the surgical treatment is in high demand. Herein we study electrochemically, microbiologically, microscopically and spectroscopically sacrificial Ag anode coatings for antibacterial implant applications. It is found that Ag dot arrays deposited on noble metals (Pd, Ir) release Ag + much faster than continuous Ag thin films. The Ag + release qualitatively scales with the difference of standard potentials between Ag and the noble metal. Furthermore, with higher numbers of Ag dots, the total amount of released Ag + increases, while the release efficiency declines. Notably, an efficient killing of Staphylococcus aureus bacteria was seen for coatings containing as little as 23 ng of Ag per mm 2 . Thus, the use of sacrificial Ag anodes as highly efficient antibacterial coating materials is evaluated. Abstract : Ag to the rescue : A highly efficient antimicrobial implant coating is investigated based on silver ion release from a sacrificial anode system. The combination of electrochemical, microbiological, force microscopic, and spectroscopic analyses allowed the quantification of efficient silver‐ion release. Thus, these innovative systems are suggested as improved antimicrobial and biocompatible coatings to prevent implant‐associated infections.